Sport tourism: an opportunity for local regions in a global context. A Delphi study (Turismo deportivo: Una oportunidad para los territorios locales en un contexto global. Un estudio Delphi) - María del Pilar Leal Londoño; Raúl Travé Molero; F. Xavier Medina; Sixte Abadia Naudí; Sheila Sánchez Bergara (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study is a research project that focus on the opportunities offered by sport tourism to invigorate local regions in a global context. Primary research data were collected through a Delphi method applied to a panel of 20 international experts on sport tourism worldwide. The results reveal that, in order to grow and become a development tool in tourism destinations, sport tourism activities need to be organised in close cooperation with sport and tourism agencies, decision makers and the local community. Moreover, that the cooperation between agencies of tourism and sport is essential to ensure the success of a sport tourism destination.